Liquid limestone in the acidity correction of a Dystric Cambisol for Brachiaria production in Humaitá, Amazonas. (Research, Society and Development, 2020)
Conventional solid limestone most commonly used in agriculture generally has disadvantages in handling, in addition to a certain infeasibility for small producers when compared to the use of liquid limestone with high purity and reactivity. Therefore, a better understanding of the dynamics of liquid limestone employed in soil acidity correction is important. Thus, this work proposes the use of liquid limestone to correct the acidity of a Dystric Cambisol in pasture cultivation in Humaitá, AM. An experiment was carried out in a greenhouse, where plastic pots were prepared for sowing Brachiaria brizantha, in a randomized block design with five treatments and four replications (T1 = witness, T2 = 2.5 L, T3 = 5 L, T4 = 10 L and T5 with common limestone). After 90 days of planting, the shoot and root size of both fresh and dry mass of each treatment were evaluated, as well as the number of tillers. The tillering of B. brizantha was highly responsive to the addition of liquid and common limestone, so that the higher the dose, the greater the results. In contrast, the treatments for fresh and dry shoot and root biomass production did not differ significantly between themselves, explaining why the product is still not well accepted and used by dealers and farmers.